Recent Advances in Application of Male Germ Cell Transplantation in Farm Animals - Ali Honaramooz; Yanfei Yang (Veterinary Medicine International)
Transplantation of isolated germ cells from a fertile donor male into the seminiferous tubules of infertile recipients can result in donor-derived sperm production. Therefore, this system represents a major development in the study of spermatogenesis and a unique functional assay to determine the developmental potential and relative abundance of spermatogonial stem cells in a given population of testis cells. The application of this method in farm animals has been the subject of an increasing number of studies, mostly because of its potential as an alternative strategy in producing transgenic livestock with higher efficiency and less time and capital requirement than the current methods. This paper highlights the salient recent research on germ cell transplantation in farm animals. The emphasis is placed on the current status of the technique and examination of ways to increase its efficiency through improved preparation of the recipient animals as well as isolation, purification, preservation, and transgenesis of the donor germ cells.